Effect of copper sulphate on the antioxidant parameters in the rainbow trout fry, Oncorhynchus mykiss - Yonar, M E; Ispir, U; Mişe Yonar, S; Kirici, M (Cellular and Molecular Biology, 2016)
The aim of this study was to evaluate antioxidant responses of rainbow trout (Oncorhynchus mykiss) exposed to different concentrations of copper sulphate (CuSO4). Fish were exposed to 0 (Group I-control), 5 (Group II), 15 (Group III) and 30 µg/L (Group IV) concentrations of CuSO4 for 14 days. Liver and gills samples were collected at the end of the experiment, and analysed for their oxidant–antioxidant status, including the malondialdehyde (MDA) level, the catalase (CAT) and glutathione peroxidase (GSH-Px) activities as well as the reduced glutathione (GSH) concentration. Results obtained showed that the levels of MDA increased in tissues of fish. Compared to control, GSH level and GSH-Px and CAT activities were significantly reduced in the fish that were exposed to different concentrations of CuSO4. The result demonstrated that CuSO4 has an oxidative-stress-inducing potential in fish.